Phosphorus fertilization of a grass-legume mixture: effect on plant growth, nutrients acquisition and symbiotic associations with soil microorganisms - Mendoza, Rodolfo Ernesto; Bailleres, Matias Andres; García, Ileana Vanesa; Ruiz, Oscar Adolfo (2018)
Adding P on Lotus tenuis and Festuca arundinacea, pure or mixed, on growth, nitrogen (N) and phosphorus (P) acquisition and associations with soil microorganisms was studied to investigate the establishment of Lotus for competing with Festuca. Triple-superphosphate was applied on a Typic Natraquoll where Lotus grows spontaneously. Biomass, N-P uptake, arbuscular mycorrhizal colonization and rhizobia nodulation were measured. Lotus achieved the highest biomass, N-P uptake in fertilized stands and Festuca the lowest in fertilized and non-fertilized stands. Mycorrhizal colonization decreased with P-fertilization in both plants. Rhizobia nodules in Lotus showed little changes with P-fertilization. In mixed fertilized-stands, Lotus promoted the growth, N-P uptake of Festuca. P-fertilization increases the ability of Festuca to compete with Lotus for available-P in soil. Lotus improves nutrient cycling, maintains high level of rhizobia nodules and arbuscular mycorrhizal colonization in roots. Adding P to limited N-P environments depress grasses growth to compete with legumes for resources